Kajian Kearifan Lokal Masyarkat dalam Pengelolaan Hutan Lindung Mutis Timau (Studi Kasus Ritual Adat (Hering) di Desa Bitobe, Kecamatan Amfoang Tengah, Kabupaten Kupang, Provinsi Nusa Tenggara Timur) - Clemens Januarius Nuhang; Ludji Michael Riwu Kaho; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
The purpose of this study is to determine the form and influence of local wisdom in Bitobe Village, Central Amfoang District, Kupang Regency, East Nusa Tenggara Province. This research was conducted in the Mount Mutis Timau Protection Forest, Bitobe Village, Central Amfoang District, Kupang Regency, East Nusa Tenggara Province. This study used unstructured form methods The data collection techniques used in this study were primary data and secondary data. From the data collected, descriptive and quantitative data analysis was carried out. The results of research by the indigenous people of Bitobe Village have long inhabited the area around the Mount Timau Forest area, from the experience of the community land cover in the Timau Forest has changed due to natural disasters. The local wisdom of the people of Timau Village affects forest sustainability, the local wisdom of the community is closely embedded in the practice of agricultural patterns and harvesting honey forest products. With the local wisdom held by the community, forest sustainability can be maintained.